POSSIBILITIES OF IMPROVING THE MECHANICAL PARAMETERS OF THE DENTAL ALLOYS - Diana Diaconu-Popa; Monica Tatarciuc; Radu Brăescu; Anca Vițalariu (Romanian Dental Association for Education, 2019)
In order to obtain metallic restorations with optimal biomechanical properties, it is necessary to transform this structure into a homogeneous solid solution, with fine crystals of equal size. The optimization of the internal architecture is therefore mandatory for obtaining metallic restorations with high durability over time. The process of optimizing the structures, casting them in to a "cold" mold, is based on the acceleration of the cooling rate, in order to increase the number of crystallization centers, and so getting internal granulations of the smallest size. For this study we used three different alloys, used for dental fixed restorations: the noble alloy Firmilay (Jelenko), which contains 74.5% gold, palladium 3.5%, silver 11% and copper 10.45%, the alloy based on cobalt-chrome- Brealloy C + B 270 chrome (Bredent), which contains 66% cobalt, chromium 20%, molybdenum 6%, tungsten 6%, silicon 0.9%, carbon 0.02% and manganese 0, 7% and Super Alloy EX-3, a nickel-chromium alloy with nickel in percentage of 59.6%, chromium 23.5%, molybdenum 9.22%, silicon 4.87% and gallium 0.46%. 20 samples were made in each alloy, 10 for the classical casting and 10 for the "cold" mould casting. The mechanical tests noticed that the samples casted in cold moulds have superior mechanical properties compared to the samples casted by the classical technology.